Feasibility Analysis of Water Play Amusement Rides of Kartika Swimming Pool, Central Java - Awatara, I Gusti Putu Diva; Hamdani, Anwar; Susila, Linda Nur; Saryanti, Endang; Pahlawi, Lukman Ahmad Imron (The journal of contemporary issues in business and government, 2021)
The government has designed various programs to improve community welfare based on local potentials and wisdom. One of the most marvelously finished products of this program is Kartika Swimming Pool in Kroyo, Sragen, Central Java. This study population were 50 employees and the manager of Kartika Swimming Pool, as well as 100 respondent by accidental sampling. The data were analyzed with financial analysis and Structural Equation Modeling-Partial Least Square (SEM-PLS). This study indicated that the level of feasibility of amusement rides is 75.5%, and 56% by visitors perception. SEM- PLS results show that price, sales promotion and service of quality have a significant effect on visitor satisfaction at Kartika Swimming Pool.